Estimating The Company Value of PT Jasa Marga Tbk - Rachmat, Satryo Sidhi; Murtaqi, Isrochmani (Journal of Business and Management, 2013)
This paper will estimate the value of PT Jasa Marga Tbk as of 1st January 2013. The author will use discounted cash flow method in order to get the company value. The main method that will be discussed is discounted cash flow method with three different scenario, most-likely, optimistic, and pessimistic scenario. The problems to be solved are the company growth for the next 5 years which will use compound annual growth rate (CAGR), a discount rate to measure the risk of the growth which will use weighted average cost of capital (WACC), and the company valuation by summarizing the discounted free cash flow and the terminal value of the company. The author will use secondary data from the companyâ€™s financial report and historical data. The results from the method are ranging from Rp. 98,762,073,184,000 to Rp. 135,772,612,523,000. From the estimated company value, the author is able to determine the share value which range from Rp.14,524 to Rp.19,967. These values are effective as of 1st January 2013. The market value of PT Jasa Marga Tbk as of 1st January 2013 is Rp.5,550. In conclusion, PT Jasa Marga Tbk has a very good value and worth for investment as the value indicates.Â Keywords: company valuation, discounted cash flow, share value.Category: Finance---------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.